International commercial tax / Peter Harris. - Harris, Peter, 1964- (Cambridge tax law series., 2020)
International Commercial Tax, 2nd edition takes account of the substantial developments of the last decade. With more than sixty percent new material, the book considers the outcomes of the OECD's BEPS project and the substantial consequential 2017 revisions of the OECD and UN Model tax treaties. With the continuing rise in the economic importance of non-OECD countries and the UK distancing itself from the EU, there has been a refocusing with less direct attention on UK domestic law and greater focus on the approaches of other significant countries, especially other common law jurisdictions. This provides greater flexibility as to how a particular point or issue is illustrated with practical examples. Greater attention is given to the UN Model, which is increasingly important. The book continues to compare the approach under model tax treaties with EU law and is updated with copious references and illustrations from the burgeoning jurisprudence of the EU Court.